Implementation of the Tikrar Method in BTQ (Guidance for Tahfidz Al Qur’an) Learning at Madrasah Ibtidaiyah - Diponegoro, Ahmad Muhammad; Khotimah, Ihda Husnul; Setiawan, Fajar Shodiq (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2024)
This article analyzes the implementation of the tikrar method in Qur’an Guidance Learning. The informants in this study were teachers and students of MIN 2 West Sumbawa. This field research utilized observation, interviews, and documentation for data collection. The data was analyzed descriptively through collection, clarification, and conclusion-drawing. The findings reveal that the tikrar method involves students memorizing one verse daily. The method is implemented both individually and in groups under the supervision of Qur’an guidance teachers. Key factors influencing the tikrar method include the understanding and application of fashohah (correct pronunciation) and tajwid (rules of recitation), consistency in the muraja’ah (review) process, the Qur’an script used for memorization, and the synergy between parents and teachers in guiding students. The study underscores the close relationship between Qur’an memorization and Islamic education, highlighting its significance as a fundamental component of the Islamic educational process.